2008
DOI: 10.1579/0044-7447(2008)37[29:mosish]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Snow in Small Headwater Catchments at Storgama, Norway: Effects on Leaching of Inorganic Nitrogen

Abstract: We have manipulated the winter-time soil temperature regime of small headwater catchments in a montane heathland area of southern Norway to study the possible effects on concentrations and fluxes of inorganic nitrogen in runoff. The experiments included extra insulation of soils in two catchments to prevent subzero temperatures during winter, and removal of snow in two other catchments to promote soil frost. Increased soil temperatures during winter increased the springtime concentrations and fluxes of ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The relatively small amount of water extracted by centrifugation limited the number of possible analyses, preventing N speciation. TDN therefore included both organic N and inorganic N, the latter amounting to 25-50 % of TDN in soil water from southern Norway Kaste et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small amount of water extracted by centrifugation limited the number of possible analyses, preventing N speciation. TDN therefore included both organic N and inorganic N, the latter amounting to 25-50 % of TDN in soil water from southern Norway Kaste et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent snow manipulation experiment in the Norwegian mountains, addition of snow induced a soil warming and resulted in increased fluxes of inorganic N during spring runoff, whereas snow removal causing soil frost had no systematic effect (Kaste et al 2008). In contrast, neither the soil warming nor soil frost in winter had a pronounced effect on concentrations and fluxes of dissolved organic carbon (DOC).…”
Section: Climate Change Effects On Inorganic Nitrogen and Doc In Runomentioning
confidence: 99%
“…In mountainous and northern regions, soil temperatures and ecosystem respiration rates tend to be higher in winters with high amounts of snowfall than in winters with less or no snow (Monson et al 2006). On the other hand, experimental snow manipulation at a mountain site in Norway indicated that no increase of inorganic N fluxes was associated with snow removal (Kaste et al 2008), suggesting that the effects of decreased snow on the N cycle varies among locations. Coherent patterns of variation in NO 3 -leaching are sometimes evident over large spatial scales and across catchments covering wide altitudinal gradients and land-use classes (e.g., Rogora et al 2008;Evans et al 2010).…”
Section: N Leaching In Dormant Seasonmentioning
confidence: 99%
“…Lake manipulation experiments have been undertaken in Canada, Norway, the USA, and Finland (e.g., Carpenter et al 2001;Harris et al 2014). There have also been a number of snow manipulation experiments in the USA, Norway, and Germany (e.g., Kaste et al 2008;Wipf and Rixen 2010). While contributing to our current understanding of N cycling in ecosystems, they also reveal significant gaps in knowledge which will require a continued commitment to long-term research and a broadening of international perspectives to address.…”
Section: Introductionmentioning
confidence: 99%